Incidence of foreign bodies in quaternary hospital patients - Dadá, Mahomed Sidique Abdul Cadar; Dadá, Abdul Habib Mahomed; Dadá, Zulaikhah Mahomed Sidique (Brazilian Journal of Science, 2024)
Foreign bodies in the ENT area are very common, in our experience, in low-income countries, for several reasons, including a lack of appropriate and suitable toys for children. The study aims to determine the epidemiological and clinical profile of patients assisted in the ENT Service with an initial diagnosis of FB, during the period 2007-2011. A descriptive, retrospective study, which goes through a collection and analysis of the data available in several registry books of patients with foreign bodies consecutively in 5 years. Results: In this study, it was observed a total of 2615 patients with foreign bodies. Most cases occur from August to November. At the end of the week, fewer cases were observed. Most of the patients were male. The most frequent complaint of patients with foreign bodies in this study was dysphagia. Metals were the most found foreign bodies and most of them were found in the esophagus. This study presents a compilation encompassing a relatively long period, constituting an important source of information on the subject. On the other hand, if we take into account the evidence of this study and the existing evidence in the literature, we can draw some conclusions that can be useful in defining prevention and control strategies of incidents by foreign bodies in natural orifices of the head and neck.